Design of P-shaped microstrip patch antenna for wireless communication systems - Raad H. Thaher; Noor Baqir Hassan (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A P-shaped microstrip patch antenna is proposed and studied to obtain operating bandwidth of (5.883-9.9) GHz. Then the antenna is extended by etching slots in the ground plane to be (5.73 – 10.234) GHz and gain varies from 2.809 dBi to 4.947 dBi. The antenna is installed on FR-4 substrate having relative dielectric constant of  = 4.3 and loss tangent of 0.02. The antenna size is (30×30×1.6)  simulation results were obtained using CST software 2016. The proposed was fabricated and tested by vector network analyzer VNA and noted reasonable agreement between simulated and measured result.